2021
DOI: 10.2147/ijgm.s324340
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Multiplicity of Thrombophilia Genetic Polymorphisms of FV, MTHFR, FII, and PAI-I: A Cross-Sectional Study on a Healthy Jordanian Population

Abstract: Background: FV, MTHFR, II, and PAI-I are the most common genes associated with thrombophilia genetic variants, which vary among different populations and ethnic groups.Little is known about the prevalence and multiplicity of these variants in Jordan. The aim of this study was to estimate the prevalence and multiplicity of the FV G1691A, FV H1299R, MTHFR 1298A>C, MTHFR 677C>T, II 20210G>A, and PAI-I 675 4G/5G variants among healthy Jordanians. Methods: This cross-sectional study was conducted on randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The prevalence of PAI1 5G/4G and FV HR2 mutations among the Palestinian population was not reported previously. Also, the prevalence of the main four IT (FVL, FII G20210A, MTHFR C677T and A1298C) among Palestinians was within the range observed in neighboring Arab countries, namely Lebanon [ 24 ], Jordan [ 42 ], Syria [ 43 ] and Egypt [ 44 ]. These neighboring Arab countries and Palestine have similar genetic backgrounds (Table 5 ).…”
Section: Discussionmentioning
confidence: 66%
“…The prevalence of PAI1 5G/4G and FV HR2 mutations among the Palestinian population was not reported previously. Also, the prevalence of the main four IT (FVL, FII G20210A, MTHFR C677T and A1298C) among Palestinians was within the range observed in neighboring Arab countries, namely Lebanon [ 24 ], Jordan [ 42 ], Syria [ 43 ] and Egypt [ 44 ]. These neighboring Arab countries and Palestine have similar genetic backgrounds (Table 5 ).…”
Section: Discussionmentioning
confidence: 66%
“…Endogamy among Jordanian society may explain the high prevalence of these mutations. In a previous study conducted on Jordanian general population, the prevalence of PAI-I 4G/5G polymorphism was 66% (Al-Zoubi et al, 2021). According to recent study, the presence of PAI-1 4G/4G polymorphism increased the risk of arterial and venous thrombosis of varied localization in infants by 48.8% and the likelihood of thrombosis by 9 folds (Filippova et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Among our cohort of healthy pregnant carriers, the most prevalent single polymorphisms were PAI-1 mutation and MTHFR, consistent with findings from other European nations. For instance, an Italian case-control study reported a 50.5% prevalence of PAI-1 gene 4G/5G polymorphisms among Italians [39], while, in a study from Jordan, the prevalence was estimated to be around 66% [40]. Wilcken et al noted an increasing prevalence of the MTHFR 6777 TT genotype in Europe, with higher rates observed in southern regions [41].…”
Section: Discussionmentioning
confidence: 99%